Intracranial Metastases Originating From Pediatric Primary Spinal Cord Glioblastoma Multiforme: A Case Report and Literature Review - Song, Dengpan; Xu, Dingkang; Gao, Qiang; Hu, Peizhu; Guo, Fuyou (Frontiers in Oncology, 2020)
Primary spinal cord glioblastoma multiforme (scGBM) is an uncommon entity in pediatrics, and intracranial metastasis originating in spinal cord gliomas is very rare. A 7-year-old female presented with weakness in the limbs, paralysis of the lower limbs and incontinence. The initial MRI of the spinal cord revealed expansion and abnormal signals from T2 to T5. She was initially diagnosed with Neuromyelitis optica spectrum disorders and treated with high-dose glucocorticoid and gamma globulin. Four months later, her symptoms worsened and follow-up imaging showed multiple intracranial mass lesions. We performed a subtotal resection of the right thalamic basal ganglia tumor and gross total resection of the right frontal lobe tumor under microscopic examination. Histopathology revealed scGBM with intracranial metastasis and the molecular pathology diagnosis suggested H3K27M mutant diffuse midline glioma WHO grade IV, which had previously been misdiagnosed as a Neuromyelitis optica spectrum disorders. We review the literature of intracranial metastases originating from pediatric primary spinal cord glioblastoma multiforme and summarize possible methods of differentiation, including changes in muscle strength or tone, intramedullary heterogeneously enhancing solitary mass lesions and cord expansion in MRI. Finally, we emphasize that in unexpected radiological changes or disadvantageous response to the treatment, a biopsy to achieve a pathological diagnosis is necessary to discard other diseases, especially neoplasms.